Nazis in Peru: from a historical past to a fallacious present - Llanos Illescas, Luis Fernando (2025)
Nazism was a German political group that caused one of the greatest genocides in the history of humanity by murdering Jews in their concentration camps; gypsies and homosexuals. Although its presence was focused on Europe, it was not limited to that territory. Many German citizens residing in Latin America, including Peru, were promoters of this ideology through their congresses and schools financed by the central government. Once the Second World War ended, Nazism lost its former splendor and became a rejected ideology. However, some Peruvian citizens have simultaneously picked up the Nazi ideology and adapted it to the Peruvian reality. In this opportunity, we will observe the presence of the Nazi ideology in the country from its beginnings to its presence in the Andean region.